2019
DOI: 10.1590/2175-7860201970077
|View full text |Cite
|
Sign up to set email alerts
|

Plantas alimentícias não convencionais (PANC) na comunidade rural de São José da Figueira, Durandé, Minas Gerais, Brasil.

Abstract: Resumo Com mais de 46.000 espécies de plantas, o Brasil tem uma das maiores diversidades biológicas do mundo. Essa imensa riqueza ainda é pouco conhecida e sua utilização como alimento tem sido negligenciada. O uso da biodiversidade local na alimentação contribui para a ampliação das fontes de nutrientes disponíveis à população e para a promoção da soberania e segurança alimentar. O presente estudo analisou o conhecimento e o uso de plantas alimentícias não convencionais (PANC) na comunidade rural de São José … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0
35

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 17 publications
0
9
0
35
Order By: Relevance
“…Different parts of plants were used in recipes however, leaves were the most commonly used part of plants employed in medicinal recipes (72.2%), followed by fruits (6.7%), among others. The predominance of the use of leaves can be related to the relative ease of obtaining them; their use was verified in other studies and is considered an important way to collect plant material since harvesting leaves is less harmful to the plant than harvesting other plant material [30,29,36,55].…”
Section: Plos Onementioning
confidence: 94%
See 1 more Smart Citation
“…Different parts of plants were used in recipes however, leaves were the most commonly used part of plants employed in medicinal recipes (72.2%), followed by fruits (6.7%), among others. The predominance of the use of leaves can be related to the relative ease of obtaining them; their use was verified in other studies and is considered an important way to collect plant material since harvesting leaves is less harmful to the plant than harvesting other plant material [30,29,36,55].…”
Section: Plos Onementioning
confidence: 94%
“…Ingestion was the most cited route of administration (77.8%). Ethnobotanical studies conducted by Silva et al [30] and Tuler [55] found that decoction was the most common method of preparation for medicinal plants. This finding was also observed in other studies, which also suggested that decoction and infusion are used because the methods are fast, easily accessible and inexpensive [44,56,57].…”
Section: Plos Onementioning
confidence: 99%
“…As plantas alimentícias não convencionais, denominadas PANC, possuem uma ou mais partes que servem como alimento para os seres humanos, desde raízes tuberosas, tubérculos, bulbos, rizomas, folhas, frutos, sementes até flores (TULER, PEIXOTO, SILVA, 2019). No Brasil, existem cerca de 3.000 espécies de PANC, sendo 350 espécies que apresentam potencial alimentar e que poderiam ser inclusas na dieta humana devido as suas características nutricionais, entre elas teores consideráveis de vitaminas, sais minerais, proteínas e fibras (KINNUP e LORENZI, 2014; BREDARIOL, 2015).…”
Section: Introductionunclassified
“…Dados históricos evidenciam que o uso de plantas para fins alimentares e medicinais teve início com o Homem de Neanderthal, extinto há 30 mil anos (HENRY et al, 2011;HARDY et al, 2012), o que revela como o uso dos recursos naturais é antigo, se mantendo até os dias atuais. Na alimentação, o uso de plantas convencionais e não-convencionais contribui para a ampliação das fontes de nutrientes disponíveis à população e para a promoção da soberania e segurança alimentar (TULER et al, 2019). Quanto às plantas medicinais, usadas no tratamento de doenças, ainda existe uma ligação entre a etnomedicina, utilizada pelos povos tradicionais, e o uso técnico-científico e comercial da biodiversidade feito pela indústria farmacêutica (ALHO, 2012).…”
Section: Introductionunclassified